Serological Evidence of Hepatitis E Virus Infection in an Indigenous North American Population - GY Minuk; A Sun; DF Sun; J Uhanova; LE Nicolle; B Larke; A Giulivi (Canadian Journal of Gastroenterology)
BACKGROUND: Hepatitis E virus (HEV) infections are thought to be uncommon in North America. Recently, HEV transmission has been reported following the consumption of deer meat. Because deer are closely related to caribou and caribou meat is a staple of the Canadian Inuit and the American Eskimo diet, the present study explored the seroprevalence of HEV infection in an isolated Canadian Inuit community.